Two different strategies of Diversispora spurca-inoculated walnut seedlings to improve leaf P acquisition at low and moderate P levels - Zou, Ying-Ning; Xu, Yong-Jie; Liu, Rui-Cheng; Huang, Guang-Ming; Kuča, Kamil; Srivastava, Anoop Kumar; Hashem, Abeer; Abd_Allah, Elsayed Fathi; Wu, Qiang-Sheng (Frontiers in Plant Science, 2023)
Walnut (Juglans regia) is an important nut tree species in the world, whereas walnut trees often face inadequate phosphorus (P) levels of soil, negatively limiting its growth and yield. Arbuscular mycorrhizal fungi (AMF) can colonize walnut roots, but whether and how AMF promotes walnut growth, physiological activities, and P acquisition is unclear. The present study aimed to evaluate the effects of Diversispora spurca on plant growth, chlorophyll component concentrations, leaf gas exchange, sugar and P concentrations, and expression of purple acid phosphatase (PAP) and phosphate transporter (PT) genes in leaves of J. regia var. Liaohe 1 seedling under moderate (100 μmol/L P) and low P (1 μmol/L P) levels conditions. Three months after inoculation, the root mycorrhizal colonization rate and soil hyphal length were 45.6−53.2% and 18.7−39.9 cm/g soil, respectively, and low P treatment significantly increased both root mycorrhizal colonization rate and soil hyphal length. Low P levels inhibited plant growth (height, stem diameter, and total biomass) and leaf gas exchange (photosynthetic rate, transpiration rate and stomatal conductance), while AMF colonization significantly increased these variables at moderate and low P levels. Low P treatment limited the level of chlorophyll a, but AMF colonization did not significantly affect the level of chlorophyll components, independent on soil P levels. AMF colonization also increased leaf glucose at appropriate P levels and leaf fructose at low P levels than non-AMF treatment. AMF colonization significantly increased leaf P concentration by 21.0−26.2% than non-AMF colonization at low and moderate P levels. Low P treatment reduced the expression of leaf JrPAP10, JrPAP12, and JrPT3;2 in the inoculated plants, whereas AMF colonization up-regulated the expression of leaf JrPAP10, JrPAP12, and JrPT3;2 at moderate P levels, although AMF did not significantly alter the expression of JrPAPs and JrPTs at low P levels. It is concluded that AMF improved plant growth, leaf gas exchange, and P acquisition of walnut seedlings at different P levels, where mycorrhizal promotion of P acquisition was dominated by direct mycorrhizal involvement in P uptake at low P levels, while up-regulation of host PAPs and PTs expressions at moderate P levels.